2014
DOI: 10.1016/j.joca.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of signaling pathways in chondrocytes based on phosphoproteomic and cytokine release data

Abstract: The analysis presented herein, leveraged high throughput proteomic data via an ILP formulation to gain new insight into chondrocytes signaling and the pathophysiology of degenerative diseases in articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…One of the previous studies suggests that both these proteins directly affect the chondrocyte metabolism during chondrogenesis and osteogenesis which might be involved in bone modelling. Inhibin beta A function as progrowth signalling molecule in chondrocytes hypertrophy [62]. Inhibin and activins are involved in different pathophysiological conditions.…”
Section: Growth Factors In Chondrocyte Development Cartilage Mainmentioning
confidence: 99%
“…One of the previous studies suggests that both these proteins directly affect the chondrocyte metabolism during chondrogenesis and osteogenesis which might be involved in bone modelling. Inhibin beta A function as progrowth signalling molecule in chondrocytes hypertrophy [62]. Inhibin and activins are involved in different pathophysiological conditions.…”
Section: Growth Factors In Chondrocyte Development Cartilage Mainmentioning
confidence: 99%
“…Thus, these studies also provided compelling evidence that the pro- and anti-inflammatory cytokines, tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), IL-4, IL-6, IL-15, IL-10, IL-13, IL-15, IL-17, IL-18, IL-21, as well as chemokines, such as monocyte chemotactic protein-1 (MCP-1), fractalkine and IL-8, transcription factors, such as NF-κB and NFAT1, members of the bone morphogenetic protein family including the BMP, WNT, GREM1, FRZB and DKK1 genes, growth factors, such as transforming growth factor-β, vascular endothelial growth factor, and epidermal growth factor [20, 21], leukemia inhibitory factor [22, 23], hormonally-stimulated pain pathways, and OA susceptibility genes, such as GDF5 , all appear to be vital components germane to the OA process [2438]. Thus, it is likely that further understanding of how a balance between the pro-inflammatory and anti-inflammatory cytokine repertoire is maintained will not only reveal the complexity inherent in regulating the destruction of synovial joints in OA, but will also be instructive for designing interventional strategies that would have been completely ignored 20 or more years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Melas et al (26) found that cultured chondrocytes may release up to 55 cytokines and other active agents either spontaneously or after stimulation by various ligands and list of growth factors produced by chondrocyte may still not be complete. Thus, in view of the powerful influence exerted by CIF both on the synovial membrane (14) and CLFs as evident in this work, further studies on its composition are needed, particularly that improved CIF like-cocktail could find application in treatment of various joint or tendon ailments.…”
Section: Discussionmentioning
confidence: 99%